The law of non-recognised states in international administrative law - Handrlica, Jakub (P.A. Persona e Amministrazione, 2023)
Very recently, the question of the applicability of normative systems, established by non-recognised states, has been quite intensively discussed in the scholarship of international private law. Here, arguments were presented in support of the notion of application of these normative systems in certain relations of private law. However, the problem is also of importance with regard to the relations of administrative law, where a product of the application of law of these entities (such as a travel passport, a university diploma, or a driving licence) may also appear. This article aims to address the problem of non-recognised states from the standpoint of international administrative law. In line with the existing scholarship, this article argues that a strict distinction must be made between the recognition of a state in the sphere of international public law on one hand and the recognition of acts issued by non-recognised states on the other. The mere fact that an entity hasn’t been recognised by the means of international public law does not automatically imply that the acts issued by the administration of such an entity can not be recognised abroad. This is in particular true in those cases where the basic human rights of an individual are concerned (the cases of humanitarian reservation). However, such recognition of acts issued by non-recognised states, can only serve to protect the rights of an individual and can not imply recognition of the entity by the executive of the concerned state.